2016
DOI: 10.1021/acsami.6b10624
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Antireflection Coating for Plastics: Partial Embedding of Mesoporous Silica Nanoparticles onto Substrate Surface

Abstract: Antireflection (AR) coating for transparent plastic substrates is constructed by partially embedding mesoporous silica nanoparticles (MSNs) onto the surface of the substrates. Simulation of optical properties of polymer substrates coated with a single-particle MSN layer indicates that the surface has a low and graded refractive index in the direction of the thickness and effectively decreases the reflectance of visible light. The MSN-coated surfaces can be prepared by exposure of the MSN-painted substrates to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In order to enhance the firmness of particles on the surface of PMMA slides, the treatment of chloroform vapor is adopted to make the particles partially embedding into the PMMA. 11 The embedded depths are controlled by tuning the volumes of chloroform. After vapor treatment, the ultrasonic processing is performed to remove the unembedded particles, thus forming a monolayer particle film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to enhance the firmness of particles on the surface of PMMA slides, the treatment of chloroform vapor is adopted to make the particles partially embedding into the PMMA. 11 The embedded depths are controlled by tuning the volumes of chloroform. After vapor treatment, the ultrasonic processing is performed to remove the unembedded particles, thus forming a monolayer particle film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The adhesion force between the large particles with sizes of above 100 nm and the substrate surface is usually weak, which is very disadvantageous for practical application. In order to enhance the firmness of particles on the surface of PMMA slides, the treatment of chloroform vapor is adopted to make the particles partially embedding into the PMMA . The embedded depths are controlled by tuning the volumes of chloroform.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayindir et al 20 coated CA showed about 95% transmission at 600 nm. Tanaka and Mizoshita 21 prepared AR coatings on transparent PMMA substrates by partially embedding mesoporous silica nanoparticles (MSNs) onto the surface; the obtained MSN-coated PMMA showed peak transmittance approaching 98%. However, the aforementioned fabrication approaches need a complicated process and take a long time and their optical and mechanical performances are not satisfactory.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are many ways used to synthesize the AR surface [1][2][3][4], but nature-inspired structures with moth-eye-shapes are typically applied to a wide range of applications [5][6][7][8][9][10]. In particular, bioinspired surfaces are applied to optical devices such as in the display panels of electronic devices [11,12], and to eco-friendly energy devices such as solar cells [13][14][15][16]. These AR surfaces of moth-eye-inspired structures have various shapes and sizes depending on the fabrication method, thus realizing increased optical performances.…”
Section: Introductionmentioning
confidence: 99%